Pediatric Dialysis Case Studies A Practical Guide to Patient Care - Warady, Bradley A.; Schaefer, Franz; Alexander, Steven R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
Edited by the same team that developed the successful Pediatric Dialysis and its second edition, this text features clinical management principles that are integral to the care of children receiving chronic dialysis. Each chapter is introduced by a case presentation that serves as the basis for key learning points that are clinically applicable and presented in a succinct manner. The topics included in Pediatric Dialysis Case Studies cover virtually all aspects of pediatric dialysis care and represent the efforts of an international group of experts with firsthand clinical expertise from all disciplines represented in the pediatric dialysis team. This resource is certain to help the clinician achieve improved outcomes for these often complex patients.
Preface -- 1. Peritoneal Access -- 2. Peritoneal Equilibration Testing and Application -- 3. Peritoneal Dialysis Prescription -- 4. Dialysis During Infancy -- 5. Hypotension in Infants on Peritoneal Dialysis -- 6. Ethical Dialysis Decisions in Infants with End Stage Kidney Disease -- 7. Catheter Exit-site and Tunnel Infections -- 8. Peritonitis -- 9. Relapsing and Recurrent Peritonitis -- 10. Peritoneal Dialysis-Associated Hydrothorax and Hernia -- 11. Ultrafiltration Failure -- 12. Encapsulating Peritoneal Sclerosis -- 13. Difficult Vascular Access -- 14. Hemodialysis Prescription -- 15. Intensified Hemodialysis -- 16. Home Hemodialysis -- 17. Myocardial Stunning -- 18. Cather Related Blood Stream Infection -- 19. Intradialytic Hypotension: Potential Causes and Mediating Factors -- 20. Dialyzer Reaction -- 21. Nutritional Management of Infants on Dialysis -- 22. Nutritional Management of Children and Adolescents -- 23. Anemia -- 24. Chronic Kidney Disease: Mineral Bone Disorder -- 25. Growth Delay -- 26. Hypertension -- 27. Cardiovascular Disease -- 28. Sleep Disorders -- 29. Highly Sensitized Dialysis Patient -- 30. Health-Related Quality of Life in Youth on Dialysis -- 31. Non-adherence -- 32. Transition to Adult Care -- 33. Pregnancy in a Woman Approaching End Stage Kidney Disease -- 34. Withholding and Withdrawal of Dialysis -- 35. Does Peritoneal Dialysis (PD) Have a Role in the Management of Acute Kidney Injury (AKI)? -- 36. Continuous Renal Replacement Therapy and AKI -- 37. Continuous Renal Replacement Therapy (CRRT) for a Neonate -- 38. Anticoagulation and CRRT -- 39. Extracorporeal Liver Dialysis in Children -- 40. Therapeutic Apheresis -- 41. Neonatal Hyperammonemia -- 42. Primary Hyperoxaluria -- 43. Intoxications -- 44. Acquired Cystic Kidney Disease.
Keywords: Medicine; General practice (Medicine).; Nephrology; Pediatrics; Medicine & Public Health; Nephrology; Pediatrics; General Practice / Family Medicine